Attitude toward violence against women considering the couple relationship of fourth grade high school students belonging to public and private school centers of Lima Metropolitana - Delgado Vásquez, Ana (2013)
The study objectives were the following ones: a) Describe the attitude toward violence against women considering the couple relationship of fourth grade high school students belonging to public and private school centers of Lima Metropolitana; b) Compare the violence attitude against the women on couple relationship among male and female of fourth grade high school students of Lima Metropolitana; c) Compare the violence attitude against the women on couple relationship of fourth grade high school students belonging to public and private school centers. The research design was the comparative descriptive considering male and female fourth grade high school students from public and private school centers of Lima Metropolitana (Alarcon, 2008; Sanchez y Reyes, 2006). The statistical sampling technique was a probabilistic two stage type, determining on the first stage on a probabilistic way the schools of each UGEL educative centers from where participants were chosen on a random way in order to be evaluated. It was made the descriptive and inferential study of the variables on study. It was find statistical significant differences attitude toward violence against women on couple relationship among students of public and private schools, also, it was find statistical significant differences on male and female student attitude.